The Role of Indonesian Legal Politics in the Development of the Indonesian Criminal Law System Based on the Fourth Principle - Asy'asri, Moh Hasyim; Ramalus, Alex; Syam, Fauzi (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The source of Indonesian criminal law comes from the Criminal Code (KUHP) whose formation is carried out by political institutions based on the aspirations of the people in accordance with the fourth principle of Pancasila or in other words, the formation of criminal law is inseparable from legal politics. This research is important to study with the aim of knowing the role of legal politics in the formation of the Indonesian criminal law system based on the fourth precept of Pancasila. The research method used is normative juridical research method using statutory approach, case approach, comparative approach, conceptual approach. The results of this study show that legal politics is the basic policy of state administrators in the field of law that will, is and has been in effect, which originates from the values prevailing in society. Legal politics cannot be separated from the formation of the Indonesian criminal law system, because the formation of criminal law is carried out by the legislative body that represents the aspirations of the community. The role of legal politics in the enforcement of the criminal law system in Indonesia is to realize the objectives of the law, namely providing justice, certainty, and expediency.